Physical activity, sedentary behaviors and dietary habits among Saudi adolescents relative to age, gender and region - Al-Hazzaa Hazzaa M; Abahussain Nada A; Al-Sobayel Hana I; Qahwaji Dina M; Musaiger Abdulrahman O (International Journal of Behavioral Nutrition and Physical Activity, 2011)
Abstract Background Few lifestyle factors have been simultaneously studied and reported for Saudi adolescents. Therefore, the purpose of the present study was to report on the prevalence of physical activity, sedentary behaviors and dietary habits among Saudi adolescents and to examine the interrelationships among these factors using representative samples drawn from three major cities in Saudi Arabia. Methods This school-based cross-sectional study was conducted during the years 2009-2010 in three cities: Al-Khobar, Jeddah and Riyadh. The participants were 2908 secondary-school males (1401) and females (1507) aged 14-19 years, randomly selected using a multistage stratified sampling technique. Measurements included weight, height, sedentary behaviors (TV viewing, playing video games and computer use), physical activity using a validated questionnaire and dietary habits. Results A very high proportion (84% for males and 91.2% for females) of Saudi adolescents spent more than 2 hours on screen time daily and almost half of the males and three-quarters of the females did not meet daily physical activity guidelines. The majority of adolescents did not have a daily intake of breakfast, fruit, vegetables and milk. Females were significantly (p < 0.05) more sedentary, much less physically active, especially with vigorous physical activity, and there were fewer days per week when they consumed breakfast, fruit, milk and diary products, sugar-sweetened drinks, fast foods and energy drinks than did males. However, the females' intake of French fries and potato chips, cakes and donuts, and candy and chocolate was significantly (p < 0.05) higher than the males'. Screen time was significantly (p < 0.05) correlated inversely with the intake of breakfast, vegetables and fruit. Physical activity had a significant (p < 0.05) positive relationship with fruit and vegetable intake but not with sedentary behaviors. Conclusions The high prevalence of sedentary behaviors, physical inactivity and unhealthy dietary habits among Saudi adolescents is a major public health concern. There is an urgent need for national policy promoting active living and healthy eating and reducing sedentary behaviors among children and adolescents in Saudi Arabia.